Comparison of training effects on elite Taekwondo players as a result of resistance training - Wang, H. H.; Lee, W. C.; Shiang, T. Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Research indicates that traditional resistance training with slow contraction velocity and deceleration phases do not effectively increase muscular power. However, both ballistic movement and functional isometric movement with a high velocity and minimal deceleration phase provided superior loading conditions for the neuromuscular system and resulted in a greater power training effect. However, the training effect of these training methods has not been evaluated on elite Taekwondo athletes. Therefore, the purpose of this study was to compare the training effects among slow ramp movement (SRM), ballistic movement (BAM) and functional isometric movements (FIM) on already highly trained Taekwondo athletes. Methods Thirty-one male Taekwondo Players from the national college of sport participated in this study and were randomly allocated to SRM group (n=11), BAM group (n=10), and FIM group (n=10). During the experimental period all subjects completed the usual Taekwondo training but different training groups had to undergo training for knee extension movements three days a week. The training program consisted of five sets with five and seven repetitions using given loads (30% ~45% of 1RM). Subject in the SRM group were instructed to lower the bar to the fixed position push the bar as rapidly as possible, then stop the bar at the end of the movement. Subject in the BAM group lowered the bar to the fixed position and pushed the bar as rapidly as possible, attempting to push the bar for maximum height. When subjects executed FIM training, they not only performed the same pattern as BAM but also performed 3 seconds of isometric contraction before moving the bar. Roundhouse kick and step roundhouse kick were measured before and after the six weeks period. When the test began, the subject stood in front of the dummy, the distance between the target dummy and the subject`s tiptoe was defined as kicking displacement. Whole-body reaction system was used as a trigger to provide the starting signal. An accelerometer was attached on the back of dummy to record the end of time when the dummy was kicked. Hence, the kicking velocity was calculated as the displacement divided by the kicking time. In addition, the velocity monitoring system was designed to obtain terminal velocity. Results SRM group`s performance did not increase significantly over the training period for either kick. However, the FIM group and BAM group increased kicking velocity and terminal velocity significantly for roundhouse kick. ANOVA with repeated measures showed that FIM group and BAM group had significantly greater training effects in kicking velocity and terminal velocity when compared to SRM group. Conclusions The results suggested that BAM and FIM training could provide superior loading conditions for the neuromuscular system and develop greater velocity training effects than SRM training.